Social accountability mechanisms and access to public service delivery in rural Africa - Esbern Friis-Hansen; Signe Marie Cold-Ravnkilde (Danish Institute for International Studies (DIIS), 2013)
This study rationale is to fill a knowledge gap about the performance of social accountability initiatives in rural Africa South of Sahara supported by foreign aid in the context of decentralization. Based on a review of available literature the study focuses on the experience of social accountability initiatives, namely public expenditure tracking surveys (PETS), participatory budgeting, community-based monitoring, participatory planning and priority setting and demand drive service provision. The study seeks to review social accountability not just as a technical tool within the context of decentralization and broader political engagement. Social accountability focuses on the demand-side of good governance by aiming to strengthen the voices of citizens to demand greater accountability and responsiveness directly from public officials and service providers. As such, social accountability can be broadly defined as citizen-led action to demand accountability for providers. Social accountability can be understood as institutional arrangements that aim to 'facilitate the participation of ordinary citizens in the public policy process'.
Keywords: 300